2023
DOI: 10.3389/fpls.2023.1119678
|View full text |Cite
|
Sign up to set email alerts
|

ZmHOX32 is related to photosynthesis and likely functions in plant architecture of maize

Abstract: HOX32, a member of the HD-ZIP III family, functions in the leaf morphogenesis and plant photosynthesis. However, the regulatory mechanism of HOX32 in maize has not been studied and the regulatory relationship in photosynthesis is unclear. We conducted a comprehensive study, including phylogenetic analysis, expression profiling at both transcriptome and translatome levels, subcellular localization, tsCUT&Tag, co-expression analysis, and association analysis with agronomic traits on HOX32 for the dissect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Rice is one of the most extensively studied crops, and many projects such as the 3K Rice Genomes Project have provided extensive genetic data for the research ( Wang et al., 2018 ). Proper distribution of photosynthetic energy can improve the efficiency of crop light use efficiency, and some studies have identified the functional genes related to chlorophyll content ( Wang et al., 2015 ), fluorescence parameters ( Hao et al., 2012 ; Wang et al., 2017 ), and photosynthesis ( Wang et al., 2020 ; Miao et al., 2023 ) through genetic mapping and natural population identification, which can greatly facilitate the research on plant productivity and food security. However, few loci or genes in these natural variations have been reported to be involved in the genetic basis of rice chlorophyll content, fluorescence parameters, and their interrelationships, and there has been a lack of comprehensive and effective analysis of the genetic basis and relationship of these traits.…”
Section: Introductionmentioning
confidence: 99%
“…Rice is one of the most extensively studied crops, and many projects such as the 3K Rice Genomes Project have provided extensive genetic data for the research ( Wang et al., 2018 ). Proper distribution of photosynthetic energy can improve the efficiency of crop light use efficiency, and some studies have identified the functional genes related to chlorophyll content ( Wang et al., 2015 ), fluorescence parameters ( Hao et al., 2012 ; Wang et al., 2017 ), and photosynthesis ( Wang et al., 2020 ; Miao et al., 2023 ) through genetic mapping and natural population identification, which can greatly facilitate the research on plant productivity and food security. However, few loci or genes in these natural variations have been reported to be involved in the genetic basis of rice chlorophyll content, fluorescence parameters, and their interrelationships, and there has been a lack of comprehensive and effective analysis of the genetic basis and relationship of these traits.…”
Section: Introductionmentioning
confidence: 99%